Aktivitas Antibakteri Minyak Atsiri Buah Andaliman (Zanthoxylum acanthopodium DC) Terhadap Bakteri Streptococcus mutans dan Propionibacterium acne - Fitri, Widya; Tarigan, Yenni Gustiani; Silitonga, Evawani Martalena; Telambenua, Fiki julfitra (Universitas Sari Mutiara Indonesia, 2022)
Andaliman fruit is a cultivation plant that functions as an antibacterial. Streptococcus mutans is a bacterium that causes dental caries which causes damage to hard tissues. Acne propionibacterium Is a bacterium that causes skin diseases that cause inflammation of tissues associated with immune systems and supports inflammation of acne. Clindamicin is a broad spectrum broad-spectrum bacteriostatic antibiotic that is active against aerobic and anaerobic microorganisms, positive and negative bacteria. Isolation of andaliman fruit essential oil using the air distillation method using a stahl tool. Antibacterial activity test using disc diffusion on MHA media by determining the diameter of the inhibition zone. The concentration of andaliman fruit essential oil used was 2.5%, 5%, 10%, 20% and 40%, with n-hexane p.a solvent and clindamicin concentration 30 μg / ml which was used as a comparison with aquadest solvent. The results showed the diameter of the combined inhibitory zones in Streptococcus mutans bacteria. With a concentration of 2.5% inhibition zone 8.8 mm, inhibition zone 5% 9.0 mm, 10% inhibition zone 10.1 mm, 10% inhibition zone 11.1 mm, 40% 14.5. In acne bacteria Propionibacterium. 2.5% inhibition zone 9.1 mm, 5% inhibition zone 9.2 mm, 10% inhibition zone 10.3 mm, 20% inhibition zone 12.6 mm, 40% 14.1. And clindamicin as a comparison has a 30.6 mm inhibitory zone in acne Propionibacterium bacteria and in Streptococcus mutans. 29.2 mm. From the results of the antibacterial activity test of andaliman essential oil at a concentration of 2.5%, 5%, 10%, 20% and 40%, able to inhibit the growth of Streptococcus mutans and Propionibacterium acne. The results of isolation of Andaliman fruit essential oil by using the Stahl tool are available 4.76% essential oil